How Much of a Role Birth Asphyxia and Chronic Antenatal Hypoxia Disorders Have in the Genesis of Cerebral Palsy? Large Prospective Study of 31,804 Antenatal Mothers Followed up Till Delivery and 30,080 Live Births Observed in Sindhudurg District (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: cerebral palsy; birth asphyxia; chronic antenatal hypoxic disorders